Rap2 as a Slowly Responding Molecular Switch in the Rap1 Signaling Cascade - Ohba, Yusuke (American Society for Microbiology, 2000)
Rap2 is a member of the Ras family of GTPases and exhibits 60% identity to Rap1, but the function and regulation of Rap2 remain obscure. We found that, unlike the other Ras family proteins, the GTP-bound active form exceeded 50% of total Rap2 protein in adherent cells. Guanine nucleotide exchange factors (GEFs) for Rap1, C3G, Epac (or cyclic AMP [cAMP]-GEF), CalDAG-GEFI, PDZ-GEF1, and GFR efficiently increased the level of GTP-Rap2 both in 293T cells and in vitro. GTPase-activating proteins (GAPs) for Rap1, rap1GAPII and SPA-1, stimulated Rap2 GTPase, but with low efficiency. The half-life of GTP-Rap2 was significantly longer than that of GTP-Rap1 in 293T cells, indicating that low sensitivity to GAPs caused a high GTP/GDP ratio on Rap2. Rap2 bound to the Ras-binding domain of Raf and inhibited Ras-dependent activation of Elk1 transcription factor, as did Rap1. The level of GTP-Rap2 in rat 3Y1 fibroblasts was decreased by the expression of v-Src, and expression of a GTPase-deficient Rap2 mutant inhibited v-Src-dependent transformation of 3Y1 cells. Altogether, Rap2 is regulated by a similar set of GEFs and GAPs as Rap1 and functions as a slowly responding molecular switch in the Rap1 signaling cascade.